2017
DOI: 10.1177/1420326x17708018
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s normal to have damp’: Using a qualitative psychological approach to analyse the lived experience of energy vulnerability among young adult households

Abstract: Seeking to promote methodological innovation in fuel poverty research, this paper reflects on the use of a novel qualitative psychological approach known as interpretative phenomenological analysis. The benefits and limitations of this methodological approach are discussed within a detailed account of findings from a small-scale study undertaken in Salford, UK. Contributing to an existing gap in the existing evidence base, the research focused on the lived experience of young adult households: a demographic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…More recently, Longhurst and Hargreaves (2019) presented a pioneering study on emotional engagements with energy poverty. This study is part of a recent rise in interest in the lived experience of energypoor households (e.g., Middlemiss and Gillard, 2015;Butler and Sherriff, 2017;Middlemiss et al, 2018;Willand and Horne, 2018;Yoon and Saurí, 2019). In most of this literature on the lived experience of energy-poor households, the actual material deprivation, and the situations of the household members as well as their coping strategies are again the focus.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Longhurst and Hargreaves (2019) presented a pioneering study on emotional engagements with energy poverty. This study is part of a recent rise in interest in the lived experience of energypoor households (e.g., Middlemiss and Gillard, 2015;Butler and Sherriff, 2017;Middlemiss et al, 2018;Willand and Horne, 2018;Yoon and Saurí, 2019). In most of this literature on the lived experience of energy-poor households, the actual material deprivation, and the situations of the household members as well as their coping strategies are again the focus.…”
Section: Introductionmentioning
confidence: 99%
“…Energy studies have rarely entered into a dialogue with the broader body of scholarship on young people, where the established literature on the “geographies of youth” (Skelton & Valentine, ) has itself shown relatively less interest in young adults (Evans, ; Hörschelmann & Refaie, ). As a whole, therefore, there is a significant gap in existing geographical knowledge about how young adults both need and use different energy services in the home, particularly when it comes to the relationship between socio‐economic hardship and their specific residential patterns (but see Butler & Sherriff, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the available platforms, Twitter is particularly useful for this, given that users tend to be younger than other social media users [ 11 ], though within our sample, a few nostalgic tweets reminiscing on previous residences indicated that some tweeters may have been older. Particularly in fuel poverty literature, the experiences of young people living in hard to heat and poor quality dwellings have been neglected [ 39 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%